2003
DOI: 10.1111/j.1365-2621.2003.tb07023.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Bile Salts by Soluble Fibers and Its Effect on Deconjugation of Glycocholate by Lactobacillus acidophilus and Lactobacillus casei.

Abstract: Binding of sodium cholate, sodium taurocholate, and sodium glycocholate by guar gum, soluble oat fiber, xanthan gum, and inulin was studied. All soluble fibers were able to bind sodium cholate, sodium taurocholate, and sodium glycocholate from a mixture of the three, but when tested individually, the fibers bound little or no sodium cholate. In general, the fibers bound higher concentrations of conjugated bile salts than they did free bile salts. Soluble oat fiber, which bound as much or more sodium cholate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In contrast, deconjugated bile (free bile salt) inhibits probiotics. Previous studies have noticed that free bile has an ability to adhere to soluble fiber [12,46]. However, in the present study in the presence of bile, the microorganisms had a moderate affinity for fiber and not only for soluble fiber but for total and insoluble fiber (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…In contrast, deconjugated bile (free bile salt) inhibits probiotics. Previous studies have noticed that free bile has an ability to adhere to soluble fiber [12,46]. However, in the present study in the presence of bile, the microorganisms had a moderate affinity for fiber and not only for soluble fiber but for total and insoluble fiber (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Thus, soluble fibre is thought to have an impact on bile salt recycling plus mixing and transport of mixed micelles ( 136 ) . It has been suggested that soluble forms of fibre exert their plasma cholesterol-lowering effect by direct ‘binding’ of polysaccharides to bile salts, although the type of binding involved here is unclear ( 136 , 145 147 ) . A more likely explanation may be that there is a temporary entrapment of the bile salts within the viscous network of entangled polysaccharide chains ( 148 151 ) .…”
Section: Specific Mechanisms Of Dietary Fibre Action Related To Macromentioning
confidence: 98%